2022
DOI: 10.5194/amt-15-383-2022
|View full text |Cite
|
Sign up to set email alerts
|

Laboratory characterisation of the radiation temperature error of radiosondes and its application to the GRUAN data processing for the Vaisala RS41

Abstract: Abstract. The paper presents the Simulator for Investigation of Solar Temperature Error of Radiosondes (SISTER), a setup that was developed to quantify the solar heating of the temperature sensor of radiosondes under laboratory conditions by recreating as closely as possible the atmospheric and illumination conditions that are encountered during a daytime radiosounding ascent. SISTER controls the pressure (3 to 1020 hPa) and ventilation speed of the air inside the wind-tunnel-like setup to simulate the conditi… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 30 publications
1
9
0
Order By: Relevance
“…Using the setup, the uncertainty of the GDP of RS41 is evaluated to be about 0.3 • C (k = 2) at 35 km. It is also found that the daytime GRUAN profile is 0.35 • C warmer than the manufacturer's at 35 km (von Rohden et al, 2022); however, the surrounding temperature, which also affects the radiation correction, cannot be changed. Furthermore, an upper-air simulator (UAS) was developed by the Korea Research Institute of Standards and Science (KRISS) to similarly evaluate radiosondes (Lee et al, 2020).…”
Section: Introductionmentioning
confidence: 83%
See 2 more Smart Citations
“…Using the setup, the uncertainty of the GDP of RS41 is evaluated to be about 0.3 • C (k = 2) at 35 km. It is also found that the daytime GRUAN profile is 0.35 • C warmer than the manufacturer's at 35 km (von Rohden et al, 2022); however, the surrounding temperature, which also affects the radiation correction, cannot be changed. Furthermore, an upper-air simulator (UAS) was developed by the Korea Research Institute of Standards and Science (KRISS) to similarly evaluate radiosondes (Lee et al, 2020).…”
Section: Introductionmentioning
confidence: 83%
“…The uncertainty of the GDP of RS92 during daytime was gradually increased from 0.2 • C at the surface to 0.6 • C at 30 km with the coverage factor k = 2 (Dirksen et al, 2014). Recently, the same group built a new simulator to investigate the solar temperature error of radiosondes (SISTER) and derived a new GDP algorithm for the Vaisala RS41 radiosonde (von Rohden et al, 2022). The setup can control the irradiance, air pressure, ventilation, sensor rotation and tilting of the light incident angle.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…It was previously observed that the temperature rise of the RS92 was initially fast due to the small thermal mass of the sensor and subsequently slow (Dirksen et al, 2014). More recently, the temperature of the RS41 oscillated when the radiosonde was rotating under irradiation (von Rohden et al, 2022). These observations are attributed to the fact that the heating of the sensor boom with a comparably large area is coupled to the heating of the temperature sensor.…”
Section: Coefficient Unitmentioning
confidence: 99%
“…Recently, the same group conducted experiments by using a new laboratory set-up including a wind tunnel with various functionalities and improved uncertainties in processing the GRUAN data for the Vaisala RS41 sensors (von Rohden et al, 2022). However, these experiments were conducted at room temperature, and thus, the influence of the ambient temperature on the radiation error was not investigated.…”
Section: Introductionmentioning
confidence: 99%